El mapa judicial como instrumento para diseñar la prestación del servicio de justicia en Colombia (2020)
Two fundamental aspects of the organization of the territory that impact on the offer of justice are analyzed: the division of the territory for judicial purposes and the distribution of judicial offices in Colombia. These aspects have been tackled tangentially in the diagnoses on judicial congestion and the functioning of the justice system in the country. They even tend to get confused but they are two concepts that are related. However, the analysis of spatial representation in justice issues is fundamental because it is a starting point to establish the strategy in the provision of the service. By knowing the territory and dividing it in a functional way, it is possible to distribute suitable loads to the offices, avoid uncoordination that affects the system in its operation, organize the access routes according to the region, and create goals or expected returns adapted to the areas.